GREEN ROOF: SIMULATION OF ENERGY BALANCE COMPONENTS IN RECIFE, PERNAMBUCO STATE, BRAZIL - Omar,Aline (2018)
ABSTRACT Green roof is a technology that consists of the use of soil and vegetation installed in the roof of buildings, being a great solution to combat heat islands. Thus, this study aimed to compare micrometeorological changes and their effect on the energy balance of non-vegetated (slab) and vegetated building roofs by means of a simulation model calculated as a function of the reference evapotranspiration (ETo), determined by the Penman-Monteith method. This research was developed between February 1 and September 30, 2016, in the Charles Darwin Building's Parking Garage, Rio Ave Empreendimentos, Recife, PE, Brazil. For this, a weather station was installed on the external building slab. On the slab, sensible, latent, and soil heat fluxes corresponded to 75, 22, and 3%, respectively, of the energy balance. In the simulated green roof, these fluxes reached values of 6, 87, and 7%, respectively. The simulation model allowed determining the energy balance for the green roof, indicating a lower sensible heat flux (69%) and a higher latent heat flux (55%) when compared to those found in the slab.